Is Danggui Safe to be Taken by Breast Cancer Patients?—A Skepticism Finally Answered by Comprehensive Preclinical Evidence - Yue, Grace Gar-Lee; Wong, Lok-Sze; Leung, Hoi-Wing; Gao, Si; Tsang, Julia Yuen-Shan; Lin, Zhi-Xiu; Law, Bonita Ka-Bo; Tse, Gary Man-Kit; Lau, Clara Bik-San (Frontiers in Pharmacology, 2019)
Angelica sinensis (AS, Danggui) has long been regarded to stimulate breast cancer growth, hence the use of AS in breast cancer patients remains a major concern for both patients and practitioners. Since safety studies of herbs would be unethical to carry out in patients, the present study aimed to investigate the potential unsafe effects of AS in a systematic pre-clinical approach. Human breast cancer cells, breast orthotopic tumor-bearing mouse models as well as primary breast cancer cells from patients’ tumors were used to evaluate the effect of AS hot water extract on the progression of breast tumors and/or growth of breast cancer cells. We showed that AS is not that stimulatory in breast cancer both in vitro and in vivo, though AS should still be used with caution in estrogen receptor-positive breast cancer patients. This novel approach of applying breast cancer cell lines, xenograft and syngeneic tumors models, as well as primary breast cancer cells from patients’ tumors in Chinese medicines safety evaluation was proven feasible. Our finding is important information for patients, Chinese medicine practitioners and clinicians on the safety use of AS in breast cancer, which will affect future clinical practice.